Validation of quality requirements through requirements-based testing with semi-formalised model - Moketar, Nor Aiza (2018)
The usage of software system and applications has increased massively to fulfill various kind of purpose for organization,business and individual.In this case, high quality software system and application are required to ensure it provides the intended functionalities.To achieve quality software system and application,a good quality of requirements needs to be defined and validated.However,it is difficult to accomplish due to the flexibility of natural language requirements that can be confusing and easily misinterpreted.This can lead to requirements-related problems such as incorrectness, incompleteness and inconsistency.These errors in requirements will produce defective software that can lead to undesirable and non-acceptance by stakeholders. Therefore,it is crucial for the software requirements to fulfill basic quality attributes such as correctness, completeness,and consistency (3Cs).Motivated from these problems,the main objective of this studyis to develop an automated approach to validate the quality of requirements through Requirements-Based Testing methodology with semi-formalized model.This studyproposes a new automated approach to assist the requirements engineer and client-stakeholders to validate the quality of requirements.For this,we generate abstract tests by integratingRequirements-based Testing (RBT) methodology and rapid prototyping with semi-formalized models:Essential Use Cases (EUCs) and Essential User Interface (EUI).Next,we have developed pattern libraries to support the automatic extraction of abstract tests from the EUC model.They are test requirements pattern library and testcase pattern library.Here,an automated tool support called TestMEReq is also developed to realize the approach.The test-authoring template to assist requirements engineer to write accurate tests is also developed.Then,a real-time collaborative approachis also integrated with the tool to encourage users’ involvement in the validation process as well as to support better communication and collaboration among stakeholders.Finally,a comprehensive evaluation of the approach,comprising experiments of correctness test and usability test were conducted.In summary,the findings of the evaluations show that our approach can contribute to the body of knowledge of requirements engineering especially in enhancing the quality of requirements at the earliest stage.It is found that the approach is able to enhance the correctness level of the elicited requirements compared to the manual approach and produce correct generation of test.The results of the usability tests show that the approach is useful and helpful in validating the quality of requirements at the early stage of software development and able to ease the requirements validation process.